2021
DOI: 10.1016/j.onehlt.2021.100318
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of neutralizing antibodies against SARS-CoV-2 in domestic cats living with owners with a history of COVID-19 in Lima – Peru

Abstract: SARS-CoV-2 can infect a variety of wild and domestic animals worldwide. Of these, domestic cats are highly susceptible species and potential viral reservoirs. As such, it is important to investigate disease exposure in domestic cats in areas with active community transmission and high disease prevalence. In this report we demonstrate the presence of serum neutralizing antibodies against the receptor binding-domain (RBD) of the SARS-CoV-2 in cats whose owners had been infected with SARS-CoV-2 in Lima, Peru, usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…This study indicated an approximate doubling of the seroprevalence to 1.4% compared to the first study, while human cases increased eightfold in the same period. The study with the highest seroprevalence of 31.7% was performed by Jara et al [ 25 ]. However, this study only included cats whose owners previously had COVID-19, thus explaining the substantially higher prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study indicated an approximate doubling of the seroprevalence to 1.4% compared to the first study, while human cases increased eightfold in the same period. The study with the highest seroprevalence of 31.7% was performed by Jara et al [ 25 ]. However, this study only included cats whose owners previously had COVID-19, thus explaining the substantially higher prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…Of all the tested cats, 12% (6/50) tested positive for the virus. Jara et al [ 25 ] found a seroprevalence of 31.7% among cats from households with a history of COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In France, Fritz and others also found that 58.8% (20/34) of tested cats and 38.5% (5/13) of tested dogs were seropositive for SARS-CoV-2 [122]; positive samples were greater among animals kept close to COVID-19-positive households. In Lima, Peru, SARS-CoV-2 antibodies were also observed in domestic cats [123]. In Germany, during the first-wave COVID-19 pandemic, antibodies to SARS-CoV-2 were detected in 0.65% (6/920) of serum samples collected from cats [124].…”
Section: Sars-cov-2 In Dogs and Catsmentioning
confidence: 99%